Era uma vez a educação inclusiva na literatura infantil - CARVALHO, Tamires Barros de (2020)
The theme Special Education, modality of education of the Basic Education, in the perspective of inclusion has gained prominence in works of literature for children. In this way, this article aims to analyze, in children's literature books, the approach taken about people with disabilities as characters in the stories. The selected books were the complementary collection of literacy and literacy in the different areas of knowledge available to public schools in the context of the National Pact for Literacy in the Right Age. The titles (ABC of animals, Lilac, a different girl, Sofia, the swallow, Who is the Glory?; Who won the game? Exploring addition and subtraction, The silent world of Flower) are for working with literacy students from 1st to 3rd year of Elementary School. Hearing impairment, visual impairment and physical disability are the most discussed topics in the works. The approach given to research is qualitative in nature and the type of bibliographic study. Based on the methodology of content analysis, the research pointed out that the books address Inclusive Education that respects differences and values the potential of people with disabilities. Another relevant aspect was the fact that children's literature enabled the formation of critical readers, from children.